The Implementation of Integrated Management of Childhood Illness (IMCI) in Sick Children with Diarrhea - Joaquim Pinto; Sayekti Wahyuningsih; Yenny Puspitasari; Joaquim Gregorio de Carvalho; Novita Ana Anggraini (Disease and Health: Research Developments Vol. 8, 2025)
According to the United Nations International Children’s Fund and World Health Organization (UNICEF, 2017), Integrated Management of Childhood Illness is the standard for Integrated Management of Sick Child when the caregiver brings the child to a health facility. Integrated Management of Childhood Illnesses (IMCI) is a program that focuses on the main childhood diseases that occur in children under five years of age with a focus on pneumonia (acute respiratory infection), diarrhea, malaria, measles, dengue hemorrhagic fever (DHF), ear and malnutrition. Diarrhea is a global health problem that causes high morbidity and mortality in developing countries due to poor environmental sanitation and hygiene, inadequate water supply, poverty and limited access to education. IMCI is a strategy that focuses on the child as a whole, not on a single disease or condition, but on a combination of illnesses that need to be treated in an integrated manner at home and in primary health care facilities. Based on the Becora Community Health Center report cases handled using the IMCI strategy totaled 2,204 cases in 2021, 4,273 cases in 2022 and 3,160 cases, from January to June 2023. Diarrhea cases ranked first, namely 584 cases in 2021, and in 2022 experienced an increase to 758 cases and until June 2023 cases of diarrhea reached 416 cases. The purpose of this residency is to know the management of cases of diarrhea by using IMCI strategies at the Becora Health Center, Dili, Timor Leste. Using descriptive studies because they only wanted to know the frequency distribution of cases handled with IMCI and specifically wanted to observe the management procedures in cases with diarrhea. Based on the results residence from 17-29 July 2023, 598 cases were not handled according to the IMCI strategy, of which 10.37% (n=62) cases had diarrhea and 0.5% (n=3) dysentery cases. In accordance with the results of observations the IMCI management procedures are not in accordance with ministry standards or policies issued by the Ministry of Health Timor Leste. During residence, it appears that health professionals conducting consultations are more directed to using general consultations than using the IMCI strategy. In conclusion, IMCI is a national program and has contributed to reducing morbidity and mortality in Timor Leste, namely until 2030, it could drop to 15/1000 live births. Lack of support for facilities and infrastructure and a lack of trained IMCI personnel can affect the management of IMCI.